Social mobility in the Philippine labor market - Dacuycuy, Lawrence B. (Philippine Review of Economics, 2018)
In this paper, we focus on the measurement and characterization of social mobility in the Philippine labor market using standard methodologies. First, we ascertain the degree to which intergenerational wage mobility can be measured using available survey data. Second, using a simple regression based approach, we determine the extent to which wages are persistent on the part of sons and daughters relative to fathers’ wage outcomes. Third, we highlight the role of parental education and measure how the labor market rewards or penalizes labor market participants. Fourth, we examine the statistical importance of parental educational achievements relative to their children using the ordered probability model.